FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR TAHUN 2018-2020 YANG TERDAFTAR DI BEI DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Geraldio, Ferick; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to analyze the effect of profitability and asset structure on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX) with firm size as a moderating variable. The research period starts from 2018 to 2020. The research sample was taken based on the purposive sampling method consisting of 70 companies. Sothe research data for three years amounted to 210 data. The data obtained were processed using the Eviews v.12.0 program. The results of the analysis in this study indicate that profitability has a positive and significant effect on capital structure. Asset structure has a positive and significant effect on capital structure. Firm size can moderate but weaken the effect of profitability on capital structure. Firm size can moderate but weaken the effect of asset structure on capital structure.